Antimicrobial and Cytotoxic activities of Jatropha curcas (Euphorbiaceae) - Gupta, Dipankar Das; Haque, Md Enamul; Islam, Md Nahidul; Mondal, Md Shakhinur Islam; Shibib, Baigid Alam (Dhaka University Journal of Pharmaceutical Sciences, 2011)
DOI: http://dx.doi.org/10.3329/dujps.v9i2.7899 Dhaka Univ. J. Pharm. Sci. 9(2): 139-142, 2010 (December)